Faktor Risiko yang Mempengaruhi Kepatuhaan Terapi Antiretroviral (ARV) pada Pasien HIV/AIDS di RSUD Abepura Jayapura - Konstantina Pariaribo; Suharyo Hadisaputro; Bagoes Widjanarko; Muchlis Achsan Udji Sofro (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2017)
Background: HIV/AIDS is a major problem in many countries. Antiretroviral (ARV) has become the solution for preventing the pandemic disease. This research aimed to ﬁnd out risk factors, which affected the HIV/AIDS patients adherence to the antiretroviral (ARV) therapy. The research took place at RSUD Abepura in Jayapura.Method: The research applied an analytical observational design with a case control, which was supported by qualitative data. There were 86 respondents involved, consisting of 43 case and 43 control respondents. Samples collection used a Simple Random Sampling. Instruments used for this study were questioners and indepth interviews. Data analysis included univariate and bivariate analyses using a chi-square test. In addition, it also performed a multivariate analysis using logistic regression test.Results: The research found three risk factors that affected the HIV/AIDS patients adherence to ARV: occupation (p = 0.005; OR = 4.472; 95% CI = 1.633-12.245), inaccessibility to health care center (p = 0.008; OR = 3.675; 95% CI = 1.476-9.146), lacking family supports (p=0.013; OR =3.606; 95% CI = 1.398-9.146). Other factors, sex, age, knowledge, apathetic manner,side-effect history, therapeutic tenure, ethnic background, counseling personnel, health care provider attitude, religious approach, alternative medicine intake, and herbal medicine use, did not have signiﬁcant affects.Conclusion: Factors that affected the ARV therapy adherence were occupation, inaccessibility to health care center, and lacking family supports.